Preliminary radiation hybrid map for river buffalo chromosome 6 and comparison to bovine chromosome 3 - Stafuzza, N. B.; Ianella, P.; Miziara, M. N.; Agarwala, R.; Schaffer, A. A.; Riggs, P. K.; Womack, J. E.; Amaral, M. E. J. (Blackwell Publishing, 2007)
We present the first radiation hybrid (RH) map of river buffalo (Bubalus bubalis) chromosome 6 (BBU6) developed with a recently constructed river buffalo whole-genome RH panel (BBURH5000). The preliminary map contains 33 cattle-derived markers, including 12 microsatellites, 19 coding genes and two ESTs, distributed across two linkage groups. Retention frequencies for markers ranged from 14.4% to 40.0%. Most of the marker orders within the linkage groups on BBU6 were consistent with the cattle genome sequence and RH maps. This preliminary RH map is the starting point for comparing gene order between river buffalo and cattle, presenting an opportunity for the examination of micro-rearrangements of these chromosomes. Also, resources for positional candidate cloning in river buffalo are enhanced.
Keywords: River buffalo; chromosome 6; radiation hybrid mapping